Eksisi Luas dan Rekonstruksi dengan Flap pada Karsinoma Sel Basal di Daerah Frontal Kanan: Laporan Kasus: Laporan Kasus - Oktavenra, Ari; Halil, Amwal (PT Kalbe Farma Tbk., 2026)
Introduction: Basal cell carcinoma is a type of non-melanoma skin cancer characterized by basaloid cells that form lobules, columns, bands, or strands. The primary goal of basal cell carcinoma treatment is to completely remove the tumor while preserving function and physical appearance as much as possible. Case: A 70-year-old man with basal cell carcinoma of the right frontal region-superior eyelid OD. Diagnosis was made based on physical examination and histopathological findings. The procedure included wide excision and frozen-section analysis of the surgical margins in the superior eyelid region and the medial canthus, with positive margins; reconstruction was performed with a rotational flap and a skin graft. Anatomical pathology results showed well-differentiated infiltrating basal cell carcinoma. The most effective therapy is surgery. Discussion: In this case, a diagnosis of mixed nodular and pigmented BCC was established based on clinical and histopathological findings, followed by surgical excision and reconstruction using an advancement flap appropriate for the defect in the frontal region. This approach yields a high cure rate; however, long-term follow-up remains necessary given the risk of recurrence and the emergence of new BCC lesions. Conclusion: Basal cell carcinoma generally grows slowly, often developing locally without spreading or metastasizing. Appropriate management can improve quality of life and life expectancy.